Role of Psychological Pain Management on Successful Paediatric Physiotherapy and Rehabilitation: A Comprehensive Review - Al Ali , Amani Abdulla Mohammed (Current Progress in Medicine and Medical Research Vol. 6, 2023)
The aim of the current study is to present a comprehensive review of extant literature touching on the role of psychological pain management on successful paediatric physiotherapy and rehabilitation. Pain is multidimensional therefore assessment must include the intensity, location, duration and description, the impact on activity and the factors that may influence the child’s perception of pain (bio psychosocial phenomenon) The influences that may alter pain perception and coping strategies include social history/issues, cultural and religious beliefs, past pain experiences and the first pain experience. The goal of the study was to gather information about the various needs of children in terms of pain management, as well as how physiotherapy practise can be used to manage pain in children both psychologically and physically. The findings of the research highlighted the important role that physiotherapy with specific focus on psychological capabilities of physiotherapist to identify pain in children and effectively manage it. Children who experience chronic pain may benefit from rehabilitation and physiological treatments, such as occupational and physical therapy, which aim to enhance physical performance by encouraging self-management of pain and gradually reintroducing previously avoided activities. This was noted to assist children in their rehabilitation process post injury including but not limited to the positive uptake of other treatment such as surgery.